Tropical forcing of Circumpolar Deep Water Inflow and outlet glacier thinning in the Amundsen Sea Embayment, West Antarctica - Steig, E.J.; Ding, Q.; Battisti, D.S.; Jenkins, Adrian (Annals of Glaciology, 2012)
Outlet glaciers draining the Antarctic ice sheet into the Amundsen Sea Embayment (ASE) have accelerated in recent decades, most likely as a result of increased melting of their ice-shelf termini by warm Circumpolar Deep Water (CDW). An ocean model forced with climate reanalysis data shows that, beginning in the early 1990s, an increase in westerly wind stress near the continental shelf edge drove an increase in CDWinflow onto the shelf. The change in local wind stress occurred predominantly in fall and early winter, associated with anomalous high sea-level pressure (SLP) to the north of the ASE and an increase in sea surface temperature (SST) in the central tropical Pacific. The SLP change is associated with geopotential height anomalies in the middle and upper troposphere, characteristic of a stationary Rossby wave response to tropical SST forcing, rather than with changes in the zonally symmetric circulation. Tropical Pacific warming similar to that of the 1990s occurred in the 1940s, and thus is a candidate for initiating the current period of ASE glacier retreat.